Mystery Stories - Chosen by Helen Cresswell and Illustrated by Adrian Reynolds (London Kingfisher Publishers, 1998)
This compilation features writers as diverse as Thomas Malory, Emily Bronte and Carl Jung. The stories are filled with extraordinary events, mysterious circumstances and eeriness. Powerful illustrations add to their atmosphere.
Include Pictures
Keywords: Children's stories -- Detective and mystery stories -- Children's stories, English